Chain Performance Analysis Supply Using the Balanced Scorecard Method in the Kachi Milk Beverage Business - Muhamad Rizky (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
One of efforts that can done to be able to sufficient need customer with method notice management chain supply in a way well, that's it This because basically​ chain supply This notice regarding the goods process until customer in a way good. In the chain supply evaluation performance becomes very important, because Can know effectiveness strategy determination and its application in the business world. The goal in study This is For analyze flow performance chain supply as well as know mark chain supply which obtained what is Kachi Milk's business ? Already Good or no. Method of analysis in study This use balanced scorecard. On the Balanced Scorecard This explain mission and tactics capable organization​ made into become business for reach objective as well as become reject measuring performance in the company. Research results This is in the form of results the average value shows that from perspective finance to obtain value 3 (enough) good), internal business process perspective obtains value 3.4 (good), perspective growth and development to obtain value 3.12 (enough) good) and perspective customer to obtain value 3.6 (good). For the total average value for all perspective is 3.28 (enough) good). Concluded that performance on the chain supply business This Kachi Milk drink Enough Good based on four perspective, the need for efforts in business Kachi Milk drink for increase performance chain to be more increase.